Andrographolide Alleviates Acute Brain Injury in a Rat Model of Traumatic Brain Injury: Possible Involvement of Inflammatory Signaling - Tao, Li; Zhang, Li; Gao, Rong; Jiang, Feng; Cao, Jianbo; Liu, Huixiang (Frontiers in Neuroscience, 2018)
Neuroinflammation plays an important role in secondary injury after traumatic brain injury (TBI). Andrographolide (Andro), a diterpenoid lactone isolated from Andrographis paniculata, has been demonstrated to exhibit anti-inflammatory activity in neurodegenerative disorders. This study therefore aimed to investigate the potential neuroprotective effects of Andro after TBI and explore the underlying mechanisms. A weight-dropping model was employed to induce TBI. Modified neurological severity scores were employed to assess the short-term neurological deficits, neuronal degeneration and apoptosis in the brain tissues were assayed with Fluoro-Jade B (FJB) and terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) staining, immunofluorescence was designed to investigate microglial activation. Expression levels of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and interleukin-6 (IL-6) were evaluated by real-time quantitative reverse transcriptase polymerase chain reaction (QPCR) and enzyme-linked immunosorbent assay (ELISA). Western blotting analysis was engaged to examine the activation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathway. Our results showed that Andro significantly attenuated neurological deficit, cerebral edema and apoptosis following TBI. Moreover, Andro administration inhibited microglial activation and expression levels of pro-inflammatory cytokines. In addition, Andro inhibited NF-κB p65 subunit translocation from cytoplasm into the nucleus and decreased the expression levels of phosphorylated extracellular signal regulated kinase (ERK) and p38 MAPK after TBI. This study suggests that Andro inhibits the NF-κB and MAPK signaling pathway to improve neurobehavioral function following TBI, which provide a new insight into the mechanism of Andro treating brain injury.